The Effect of Profitability, Free Cash Flow and Investment Opportunity Set on Dividend Policy on Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Miharto, Eko; Affan, Nurita; Sari, Dhina Mustika (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to obtain empirical evidence about the effect of the Effect of Profitability, Free Cash Flow and Investment Opportunity Set on Dividend Policy in Manufacturing Companies. This research is a quantitative study using the annual financial statements of companies listed on the Indonesia Stock Exchange (IDX). The sampling technique uses purposive sampling. The samples used were 13 Manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2018 period, so that 39 company data were obtained. Data analysis techniques used multiple linear regression. The results of this study indicate that profitability has a negative and not significant effect on dividend policy, free cash flow has a positive and not significant effect on dividend policy and investment opportunity set has a positive and significant effect on dividend policy